MODEL PEMBELAJARAN LANGSUNG TERHADAP KEMAMPUAN BINA DIRI SISWA TUNAGRAHITA - Cendika Raharjo, Rizqha (Jurnal Pendidikan Khusus, 2016)
ABSTRACTThe purpose of research was to observe whether there was influence of direct learning model toward self-guide ability model to the mentally retardation students of class VII in SLB B/C Siti Hajar Sidoarjo or not.This research used pre experiment kind with one group pre test – post test design.Based on the research, it indicated that the average value of pre test toward six subjects observed got low value i.e. 57% whereas the average value of post test toward six subjects observed after giving intervention through direct learning model got value, 89%. This indicated that there was influence of direct learning model toward self-guide ability to mild mentally retardation students in SLB B/C Siti Hajar Sidoarjo.Keywords: Direct learning model, self-guide